ORGANIZATIONAL CULUTRE IN SMEs: AN INVESTIGATION OF MANAGERS VS EMPLOYEES’ PERCEPTIONS - Mileva, Ivona; Hristova, Snezhana (The European Journal of Applied Economics, 2022)
Purpose. This paper aims to assess the organizational culture exposed by small and medium sized companies (SMEs). With other words, we examine the relationship between leadership styles, organizational culture and organizational performance. In order to investigate the role of organizational culture, it is fundamental to analyze the leadership styles in relation to the types of culture, to identify how these are related and well aligned so that they can help the SMEs to be more effective, favoring their innovativeness. Therefore, we like to address the issue of organizational alignment as well, which occurs when employees and leadership are on the same pages regarding an organization’s purposes and core values. Methodology. Based on a sample of 408 Macedonian managers and employees and using the organizational culture assessment instrument VOX, the key findings show that the dominant culture in Macedonian small and medium sized businesses is the Entrepreneurial Democracy, and that all employees share similar perceptions about organizational culture. Contribution/Value. It contributes to the scientific body of knowledge in the context of organizational culture and alignment. The implications of this study will be especially important for the Macedonian SMEs managers and owners in order to gain access to important knowledge of its the organizational culture or they need to make improvements in order to stimulate the innovativeness of their employees to participate in the improvement of company’s performance on one side and with satisfied employees on the other side. It also provides the readers with an understanding of how to measure organizational culture and its alignment through introducing up-to-date scientific research in the same field.